2011, No. 9, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Auditing theory and practice Jonas Mackevičius, Danutė Adomavičiūtė, Peculiarities and role of Lithuanian customs audit in the customs control process, 7 Irmantas Aleliūnas, Zenona Atkočiūnienė, Information audit: modelling of standards structure, 18 Vaclovas Lakis, Financial information, reasons and methods of manipulations, 33 Accounting theory and practice Indrė Kalinovaitė, Kristina Rudžionienė, Recognition and valuation of goodwill in accounting of Lithuanian companies, 46 Asta Mockevičiūtė, Kristina Rudžionienė, The impact of accounting policy on earnings management, 54 Justina Aleliūnaitė, Izolda Bučytė, Organization of accounting system in China, 62 Erika Gerasimovič, Jurgita Kunigėlytė, Organization of accounting in the Republic of Moldova, 71 Economical problems Alina Warelis, Analysis of changes in resources and productive functions of forests in Poland, 84 Donatas Ratkevičius, Software related criteria for selecting enterprise resource planning systems, 97 Rasa Subačienė, Analysis of travel agencies and travel operators‘ activity, 112 Vilius Savickas, Target costing: significance, principles and stages, 119 Jonas Martinavičius, Reda Blažaitytė, Reliability and validity assessment in financial ratios analysis, 137 Rasa Kanapickienė, Development of models of internal control, 157 Reviews Daiva Raziūnienė, Audit and analysis of financial statement: professional approach to financial statements, 172